A SIMPLIFIED READING ON TSAO HSUEH-CHINS NARRATOLOGY IN HUNGLOUMENG ( ) OF DREAM OF THE RED CHAMBER - Mulyani, Sri (Universitas Sanata Dharma, 2014)
This article attempts to analyze the narrative aesthetics in Tsao Hsueh-Chins Hung Lou Meng or Dream of the Red Chamber through a feminist framework. Hung Lou Meng written in the mid-18th century is regarded to be one of the best and famous Chinese novels. Among several studies on Hung Lou Meng, there are at least two different perspectives that in fact is rooted in the old theoretical battle in viewing literature: one as a mimesis and the other as a linguistic construct. Employing feminist narratology, this article ventures to bridge those two different opposing views to unveil the narrative discourse of Hung Lou Meng. This feminist perspective reveals the rich artistic quality of Hung Lou Meng as well as its flexibility, fluidity, polyphony, and dialogical qualities that enable to liberate different voices present simultaneously including those of the muted and oppressed gender.Keywords : Asian Novel, Narrative Discourse, Feminist Perspective